2011
DOI: 10.1007/s00436-011-2623-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of selected Lamiaceae and Zingiberaceae plant essential oils against the dengue vector Aedes aegypti L. (Diptera: Culicidae)

Abstract: The larvicidal activity of hydrodistillate extracts from Mentha piperita L. Ocimum basilicum L. Curcuma longa L. and Zingiber officinale L. were investigated against the dengue vector Aedes aegypti L. (Diptera: Culicidae).The results indicated that the mortality rates at 80, 100, 200 and 400 ppm of M. piperita, Z. officinale, C. longa and O. basilicum concentrations were highest amongst all concentrations of the crude extracts tested against all the larval instars and pupae of A. aegypti. Result of log probit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Hence, there has been an increasing interest in the development of alternative methods of mosquito control which are less hazardous to humans and other living organisms. In this regard, plantderived compounds have emerged as good candidates, not only as new effective tools in vector management but also as environmentally safer agents (Garcez et al 2009;Govindarajan et al 2011;Kalaivani et al 2011;Prophiro et al 2011;Kanis et al 2011). The present study evaluated the effect of a novel herbal formulation PONNEEM prepared from A. indica and P. glabra oils to minimize human vector mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, there has been an increasing interest in the development of alternative methods of mosquito control which are less hazardous to humans and other living organisms. In this regard, plantderived compounds have emerged as good candidates, not only as new effective tools in vector management but also as environmentally safer agents (Garcez et al 2009;Govindarajan et al 2011;Kalaivani et al 2011;Prophiro et al 2011;Kanis et al 2011). The present study evaluated the effect of a novel herbal formulation PONNEEM prepared from A. indica and P. glabra oils to minimize human vector mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
“…A quantity of reports establish the mosquito larvicidal potential of the plant extracts and the essential oils obtained from the different parts of the range of plants (Amer and Mehlhorn 2006b, c;Kalaivani et al 2012;Thanigaivel et al 2012;Mann and Kaufman 2012;Pradeepa et al 2014Pradeepa et al , 2015 though the insecticidal effects of plant chemicals differ not only according to plant species, mosquito species and plant parts but also to extraction methods. Previous investigations have indicated that various Piper nigrum and P. guineense are used as insecticides and molluscicides in different parts of Africa, while in India species like P. longum, P. betle and P. cubeba have shown insecticidal activity against mosquitoes and flies (Lee 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mosquito species Culex quinquefasciatus Say is the most important vector of the filarial parasite Wuchereria bancrofti and a variety of arboviruses on the East African coast and the islands of the Indian Ocean, including Zanzibar (Jones et al 2012;Kalaivani et al 2012). Synthetic insecticides used for mosquito control are derived from those developed for agriculture and are very often based on organophosphates, pyrethroids, organochlorines, carbamates or cyclodienes (McAllister & Adams 2010).…”
mentioning
confidence: 99%
“…Selection of the most suitable and effective chemotypes is the key factor in ensuring proper plant material, which would be cultivated as a source of active compounds of botanical insecticides. The effects of different EO from the genus Mentha L. against the larvae and adults of mosquitoes have been studied (Koul et al 2008;Pavela 2008a,b;Kalaivani et al 2012). However, to our knowledge, there is no previous study focused on selecting the most suitable chemotype among the commercially available taxa.…”
mentioning
confidence: 99%